Bayesian Updating for Probability of Failure of Jacket Platforms in Malaysia - Kurian, V.J. (2013)
Abstract- The Jacket platform codes such as API LRFD and ISO 19902 are based on probabilistic design of component and joint reliability. They consider overall structural integrity, redundancy and multiple failure paths only indirectly by using structural integrity assessment methods. In this paper, probability of failure is determined as per design requirement of 100 year extreme conditions using Monte Carlo simulation. To get information on maximum strength, maximum wave height was increased till the reserve strength ratio reached 1, using SACS pushover analysis. Stokes’s 5th order theory and Morrison Equation were used for finding the environmental loads. Regression analysis was used for the load model using surface fit tool of Matlab. The wave which gave an RSR value of 1 is considered as the maximum wave, the jacket can withstand with the available resistance of material. This theory has already been applied on land based structures, such as proof loading used against existing structures to gauge the strength of structure. This new maximum wave height has been used to find the updated failure probability and compare it with failure probability of design wave. The study covers one platform, and recommendation is made whether the platform is suitable for the extension of life or not. This study can further lead to updating based on new information on material resistance of platforms. Keywords: Jacket platform; Probability of failure; Environmental loading; reserve strength ratio; Bayesian updating